POSSIBILITIES OF APPLICATION OF DARKFLOOR LIGHTING FOR ANALYSIS OF UNLINKED OBJECTS - A. G. Anisovich (Литьë и металлургия)
The question of the metallographic researches of unconnected objects using dark-field illumination is considered.